Genotype-Phenotype Correlation in Idiopathic Cerebral Palsy: Genotype–Phenotype: Idiopathic Cerebral Palsy - Sarwat, Madiha; Farid, Aisha; Maqbool, Shazia; Rahman, Fatima; Efthimyou, Stephanie; Houlden, Henry (Pakistan Journal of Health Sciences, 2026)
Genetic etiology is an important cause of idiopathic cerebral palsy, especially in consanguineous populations. Objectives: To determine the genotype-phenotype correlation in idiopathic cerebral palsy at a tertiary care hospital in Lahore, Pakistan. Methods: This retrospective descriptive cross-sectional study was conducted in the Department of Developmental and Behavioral Pediatrics, University of Child Health Sciences, Lahore. The data on cerebral palsy children with Whole Exome Sequencing was collected from January 2022 to January 2025. The study duration for all patients with reports available from March to August 2025 was included using nonprobability consecutive sampling. Results: Eighty-two patients were included after receiving their whole exome sequencing reports, and 35 genes were identified in 58 patients, showing a diagnostic yield of WES as 70.2%. There were 52 (63.4%) males. The average age was 8.3 ± 4.1 years (SD). The phenotype of positive patients showed spastic cerebral palsy to be the most common (79%), with a predominant quadriplegic subtype (55%). Seventeen genes (SYNE 1, PYCR2, PTS, SEPSECS, MOCS1, SERAC1, DEGS1, ECHS1, HPDL, ALS2, BLM, ITPA, PARD3, RIF1, CHD2, RAB3GAP1, ADAD2, WDR62) were associated with quadriplegic type, five (TBC1D14, CENPJ, ADAMDEC1, AMPD2 and TKTL1) with spastic diplegic, five (BICRA, ADGRG, CENPF, MAGEL2, TXNDC11) with hemiplegic, five (MIX23, EXOSC8, METTL5, GNG7, EZH1) with dyskinetic and two (SLC25A12, LPIN1) with mixed type. Conclusions: Epilepsy was present in 69%, feeding issues in 84%, drooling in 74%, recurrent chest infections in 60%, sleep issues in 60%, and constipation in 79%. GMFCS level V and MACS level V were the most common. Genotype–phenotype correlations in idiopathic cerebral palsy will help in comorbidity management and prognosis.